Acute relaxation during pregnancy leads to a reduction in maternal electrodermal activity and self-reported stress levels - Ilena Bauer; Julia Hartkopf; Anna-Karin Wikström; Nora K. Schaal; Hubert Preissl; Birgit Derntl; Franziska Schleger (BMC, 2021)
Abstract Background Prenatal maternal stress can have adverse effects on birth outcomes and fetal development. Relaxation techniques have been examined as potential countermeasures. This study investigates different relaxation techniques and their effect on self-reported stress levels and physiological stress levels in pregnant women. Methods In this cross-sectional study, 38 pregnant women in their 30th to 40th gestational week were assigned to one of three, 20-min lasting relaxation groups: listening to music (N = 12), following a guided imagery (N = 12) or resting (N = 12). The intervention, i.e., acute relaxation (music, guided imagery or resting) took place once for each study participant. Study inclusion criteria were age over 18 years, German speaking, singleton and uncomplicated pregnancy during the 30th and 40th week of gestation. The stress levels were determined during the study. Current stress level during the study was assessed by a visual analogue scale. Chronic stress levels were assessed by the Trier Inventory of Chronic Stress and the Pregnancy Distress questionnaire. Multivariate analyses of covariance were performed and dependent measures included stress levels as well as physiological measures, i.e., cardiovascular activity (electrocardiogram) and skin conductance levels. Results All three forms of relaxation led to reduced maternal stress which manifested itself in significantly decreased skin conductance, F(3,94) = 18.011, p = .001, ηp 2 = .365, and subjective stress levels after the interventions with no significant group difference. Post-intervention stress ratings were further affected by gestational age, with less subjective relaxation in women later in gestation, F (1, 34)=4.971, p = .032, ηp 2 = .128. Conclusion Independent of relaxation technique, single, 20-min relaxation intervention (music, guided imagery or resting) can significantly reduce maternal stress. Notably, women at an earlier stage in their pregnancy reported higher relaxation after the intervention than women later in gestation. Hence, gestational age may influence perceived stress levels and should be considered when evaluating relaxation or stress management interventions during pregnancy. Trial registration Not applicable.